Theological dictionary of the Old Testament ; v. V - Botterweck, G. Johannes; Ringren, Helmer; Green, David E. (Grand Rapids, MI Eerdmans, 1986)
Contents : v. V : hmr - YHWH Includes bibliographical references.
Translated from Theologisches Worterbuch zum Alten Testament Band IV, Lieferungen 5-9 published 1983-84 by Verlag W. Kohlhammer GMBH, Stuutgart, W. Germany.
Keywords: Bible. O.T. -- dictionaries -- Hebrew; Hebrew language -- dictionaries -- English